The concept of Taḥawwul as a determinant for ruling of Halal for food and veverages produced through fermentation process - Iswandi Harahap, Iswandi; Muhamad Shukri, Abdul Salam; Jamaludin, Mohammad Aizat; Mohammad Nawawi, Norazah (Usuli Faqih Research Centre PLT., 2020)
Taḥawwul is a concept of transformation of determining the halal and haram status of a product produced through fermentation. There are several foods and beverages product produced through fermentation process. During fermentation process many products are produce and its status ruling of this product are different at every fermentatation stage. The objectives of this study were to identify and evaluate the taḥawwul concept as halal determination of the product produced by fermentation process. An explicit taḥawwul-based approach through taḥawwul ibtidā', taḥawwul al-wusṭā, taḥawwul al-akhīr and taḥawwul shubhah has been the basis for the halal determination of a fermentation product. To determine the effectiveness of this concept, the study was conducted by applying two samples of traditionally produced palm vinegar originated from Bestari Jaya Selangor and Penaga Pulau Pinang based on the residue of alcohol and acetic acid in the final product detected by Gas Chromatography. The results of this study found that palm vinegar from Bestari Jaya Selangor was categorized as fasīd vinegar (haram) because it was still in the taḥawwul fasīd level that the ethanol content of this vinegar exceeded the JAKIM's permissible level of 1.93% v / v while palm vinegar Penaga Pulau Pinang is categorized as ṣaḥīḥ vinegar (halal) vinegar as it has entered taḥawwul ṣaḥīḥ level as the ethanol content in this vinegar is only 0.17% v / v. Therefore, the concept of taḥawwul is very relevant as a concept to determine the ruling of products produced through fermentation process especially vinegar products.